Analysis of hybrid offshore renewable energy sources for power generation: A literature review of hybrid solar, wind, and waves energy systems - Hifsa Khurshid; Bashar S. Mohammed; Ahmad Mahamad Al-Yacouby; M.S. Liew; Noor Amila Wan Abdullah Zawawi (Developments in the Built Environment, 2024)
The overuse of conventional fuels (coal, petroleum products, and gas) for energy generation causes natural resource depletion and global warming. Therefore, the utilization of Renewable Energy Sources (RES) in power systems is seeing rapid growth on a global level, particularly in offshore locations. This work aims to review the progress in developing hybrid RES power systems in offshore environments and optimization methods used for power generation using solar, wind, and wave energy systems. The papers published in peer-reviewed journals were collected from 2000 to 2023. A total of 143 articles were obtained and analyzed. The results demonstrated a rising trend in annual publications about the use of hybrid RES in electricity generation since 2007. The hybrid solar-wind and wind-wave energy systems have received a lot of attention due to technical advancements already developed for the wind energy system. Machine learning techniques, such as genetic algorithms (GA) and particle swarm optimization (PSO), have been extensively utilized in the field of renewable energy systems for tasks such as optimizing unit sizes, determining appropriate unit placements, minimizing costs, and maximizing power output. The methods are preferred due to their less complex structure. However, the practical application, true cost estimation and installation and maintenance studies at offshore locations are poorly developed. Also, the hybrid solar-wave and solar-wind-wave RES systems need further investigations for optimal mixing at the feasibility stage. The current review is the first of its kind, focusing on offshore renewable energy systems only.